Dapagliflozin Alleviates Myocardial Ischaemia Reperfusion Injury by Activating Mitophagy via the AMPK-PINK1/Parkin Signalling Pathway - Zuo, Wei; Wang, Liang; Tian, Ran; Wang, Lun; Liu, Yifan; Qian, Hao; Yang, Xinglin; Liu, Zhenyu (Current Vascular Pharmacology, 2024)
Introduction: Myocardial ischaemia reperfusion injury (MIRI) determines infarct size and long-term outcomes after acute myocardial infarction (AMI). Dapagliflozin, a sodium-glucose cotransporter 2 inhibitor, alleviates MIRI in animal models. Method: We investigated the potential mechanisms underlying the cardioprotective effect of dapagliflozin against MIRI, focusing on mitochondrial injury and mitophagy. MIRI mouse and H9C2 cell models were established. Results: 2,3,5-Triphenyltetrazolium chloride (TTC) staining showed a significant alleviation of MIRI after pre-treatment of dapagliflozin compared to the model group (14.91 ± 1.76 vs. 40.47 ± 3.69%). Data from the pre-treatment dapagliflozin group showed a significant decrease in left ventricular ejection fraction (LVEF) (44.8 ± 2.7 vs. 28.5 ± 5.3%, P<0.01), left ventricular end-diastolic volume (LVEDV) (70.6 ± 9.5 vs. 93.5 ± 13.8 ul, P<0.05), and left ventricular end-systolic volume (LVESV) (39.0 ± 8.3 vs. 67.9 ± 13.7 ul, P<0.05) compared to the model group. Dapagliflozin also reduced the levels of reactive oxygen species (ROS) and fragmented mitochondrial DNA, reversed the decrease in mitochondrial membrane potential, and suppressed apoptosis. Further study showed that dapagliflozin could protect against mitochondrial injury by rapidly clearing damaged mitochondria via mitophagy in a phosphatase and tensin homologue (PTEN)-induced putative kinase 1 (PINK1)/parkindependent manner. Dapagliflozin regulated mitophagy in cardiomyocytes by suppressing the adenosine 5’monophosphate-activated protein kinase (AMPK)-PINK1/parkin signalling pathway, resulting in attenuated MIRI. Conclusion: Dapagliflozin alleviated MIRI by activating mitophagy via the AMPK-PINK1/parkin signalling pathway.
Keywords: mitochondria